Proyek Pemasaran Digital untuk Meningkatkan Brand Awareness Dengan Implementasi Media Sosial dan Iklan Digital pada UKM Esmart Apparel di Kabupaten Tangerang - Alyaa Nur Nasywaa Pramadhini Mukmin; Naufal Eka Firdaus; Chindy Fathmulia Diraja (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This report discusses a digital marketing project aimed at enhancing brand awareness for the SME Esmart Apparel through the implementation of social media and digital advertising. The main focus of this project is the use of Instagram and TikTok, which are two social media platforms with the largest number of active users in Indonesia. By employing a marketing strategy centered on visual content, particularly videos, it is expected to capture audience attention and increase interaction with the brand. Although Esmart Apparel has significant potential, there are several weaknesses, such as a lack of recognition outside of Tangerang Regency and budget constraints for marketing. Therefore, this report aims to provide insights and useful strategies for the development of digital marketing for SMEs in Indonesia, as well as to encourage brand growth in a broader market.